The wee divergence: Business creation and political turmoil in Ireland before 1900 - R. J. C. Adams; Gareth Campbell; Christopher Coyle; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2022)
What effect does political instability in the form of a potential secession from a political union have on business formation? Using new measures of business creation and political instability in Ireland during the late nineteenth-century, we test whether increased political instability arising from the Home Rule movement resulted in reduced entrepreneurial activity and business investment. We find that increased political instability led to a significant divergence of business creation between Scotland and Ireland. Our findings suggest that the effects of political instability on entrepreneurship were most acute in the parts of Ireland that were most concerned by potential changes.
Keywords: D80; L26; N43; N93; 330; Ireland; Scotland; Home Rule; entrepreneurship; political risk; uncertainty